Three Dose Levels of a Maternal Respiratory Syncytial Virus Vaccine Candidate Are Well Tolerated and Immunogenic in a Randomized Trial in Nonpregnant Women. (19th June 2021) - Schwarz, Tino F; Johnson, Casey; Grigat, Christine; Apter, Dan; Csonka, Peter; Lindblad, Niklas; Nguyen, Thi Lien-Anh; Gao, Feng F; Qian, Hui; Tullio, Antonella N; Dieussaert, Ilse; Picciolato, Marta; et al.
Abstract: Background: Respiratory syncytial virus (RSV) causes respiratory tract infections, which may require hospitalization especially in early infancy. Transplacental transfer of RSV antibodies could confer protection to infants in their first months of life. Methods: In this first-in-human, placebo-controlled study, 502 healthy nonpregnant women were randomized 1:1:1:1 to receive a single dose of unadjuvanted vaccine containing 30/60/120 µg of RSV fusion (F) protein stabilized in the prefusion conformation (RSVPreF3) or placebo. Results: Solicited local adverse events (AEs) were more frequently reported in the RSVPreF3 groups (4%–53.2%) versus placebo (0%–15.9%); most were mild/moderate. Unsolicited AEs were comparably reported among groups. Three serious AEs were reported; none was vaccination-related. Compared with prevaccination values, anti-RSV A neutralizing antibody geometric mean titers and anti-RSVPreF3 immunoglobulin G geometric mean concentrations increased 8- to 14-fold and 12- to 21-fold at day 8 and persisted 5- to 6-fold and 6- to 8-fold higher until day 91 in the RSVPreF3 groups versus 1-fold in placebo. Comparisons at day 8 and day 31 showed that the higher dose levels were significantly more immunogenic than the lowest one. Conclusions: The RSVPreF3 vaccine was well tolerated and immunogenic. The 60 and 120 µg dose levels were selected for further investigation in pregnant women. Clinical Trials Registration: NCT03674177. Abstract : In this first-in-human, placebo-controlled study, 30, 60, or 120 µg of unadjuvanted RSVPreF3 vaccine were well tolerated and immunogenic. Dose levels 60 and 120 µg were significantly more immunogenic than 30 µg and selected for further investigation in pregnant women.